Analysis of Designed Power System with the Real Power System - Dr. Raja Singh Khela, Sandeep Kaur (International Journal of Advanced Science and Technology, 2019)
This Research deals with the investigation of designed power system with the real power system of 11 KV substation at Sahnewal . It used an optimization technique to reduce the fault in voltage and current. The collapse of the voltage and the swelling of the current constitute the main problem of nonlinear loads.Thus, by study Grey wolf optimization technique we have to reduce the difficulty of sag / swell of the voltage and current by using the static distribution compensator (D-STATCOM). The result of optimization technique in mitigating voltage sag/ swell is find out with the help of MATLAB simulation .This paper presents the 3 phase fault of voltage and current that occur in 11kv substation at Sahnewal are removed by using Grey wolf optimization technique, and also compared the results  with real Power system.  Keywords: D-STATCOM, energy storage device (ESD),Grey wolf optimization technique, Voltage Sag, voltage swell,   MATLAB/SIMULINK